Dose-response meta-analysis on coffee, tea and caffeine consumption with risk of Parkinson's disease - Qi, Hui; Li, Shixue (Geriatrics & gerontology international, 2014)
Aims A dose–response meta‐analysis was carried out between Parkinson's disease (PD) risk, and coffee, tea and caffeine consumption. Methods A comprehensive search was carried out to identify eligible studies. The fixed or random effect model was used based on heterogeneity test. The dose–response relationship was assessed by restricted cubic spline. Results A total of 13 articles involving 901 764 participants for coffee, eight articles involving 344 895 participants for tea and seven articles involving 492 724 participants for caffeine were included. A non‐linear relationship was found between coffee consumption and PD risk overall, and the strength of protection reached the maximum at approximately 3 cups/day (smoking‐adjusted relative risk: 0.72, 95% confidence interval 0.65–0.81). A linear relationship was found between tea and caffeine consumption, and PD risk overall, and the smoking‐adjusted risk of PD decreased by 26% and 17% for every two cups/day and 200 mg/day increments, respectively. The association of coffee and tea consumption with PD risk was stronger for men than that for women, and the association of caffeine consumption with PD risk was stronger for ever users of hormones than that for never users of hormones among postmenopausal women. The aforementioned associations were weaker for USA relative to Europe or Asia. Conclusions A linear dose‐relationship for decreased PD risk with tea and caffeine consumption was found, whereas the strength of protection reached a maximum at approximately 3 cups/day for coffee consumption overall. Further studies are required to confirm the findings. Geriatr Gerontol Int 2014; 14: 430–439.